2011
DOI: 10.1167/iovs.10-5842
|View full text |Cite
|
Sign up to set email alerts
|

Response of Retinal Vessels and Retrobulbar Hemodynamics to Intravitreal Anti-VEGF Treatment in Eyes with Branch Retinal Vein Occlusion

Abstract: BRVO is an ischemic retinal disease. Given that ranibizumab treatment reduces retinal perfusion in these eyes the potential long-term effects of this vasoconstriction need to be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 33 publications
5
61
0
2
Order By: Relevance
“…Even if cataract surgery is not estimated as a major problem today, the increased risk of postoperative CME or endophthalmitis, especially in diabetic patients, should be considered. On the other hand, it is proven that bevacizumab, even if delivered in minimal vitreal concentrations, downregulates VEGF plasma levels 17 and may provoke cardiovascular events, 18,19 as diabetic patients are innately exposed to increased cardiovascular risk factors. The therapeutic mechanisms of the drugs and the retinal structures are comparable, but not identical.…”
Section: Discussionmentioning
confidence: 99%
“…Even if cataract surgery is not estimated as a major problem today, the increased risk of postoperative CME or endophthalmitis, especially in diabetic patients, should be considered. On the other hand, it is proven that bevacizumab, even if delivered in minimal vitreal concentrations, downregulates VEGF plasma levels 17 and may provoke cardiovascular events, 18,19 as diabetic patients are innately exposed to increased cardiovascular risk factors. The therapeutic mechanisms of the drugs and the retinal structures are comparable, but not identical.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no firm consensus on a repeat injection algorithm for this group of patients, caution should be taken, since injections of anti-VEGF agents may carry some additional deleterious effects. We should take into account that BRVO is an ischemic retinal condition, and that anti-VEGF agents may reduce retinal perfusion, causing a paradoxical harmful effect in these patients [28]. Moreover, repeated injections of VEGF inhibitors might also lead to retinal atrophy secondary to obstruction of neuroprotective cytokines and regression of normal vasculature [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…However, Mete et al [17] found no blood flow changes 1 day after the injection. Another study also demonstrated a reduction in blood velocity in the central retinal artery starting 1 week after intravitreal ranibizumab injection in patients with branch retinal vein occlusion [20]. Therefore, it is conceivable that an intraocular injection of anti-VEGF agent further compromised retinal circulation, which was already highly impaired, and resulted in retinal artery occlusion in these cases with retinal vascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Neovascular glaucoma usually develops in eyes with severe ocular ischemia, which causes a marked increase in intraocular VEGF [13][14][15]. Histological and physiological evidence is accumulating that indicates suppression of VEGF by intraocular injection of anti-VEGF agents may cause reduced blood flow in the retina or choroid [16][17][18][19][20]. Therefore, safety concerns, especially to ocular ischemic events, may be necessary in patients with neovascular glaucoma.…”
Section: Introductionmentioning
confidence: 99%